The impact of a specialized inpatient and day patient group programme on clinical outcome in older adolescents and young adults with mental illness. (2nd March 2016) - McCrossan, P.; Ryan, A.; Connellan, M.; Power, P.
Abstract : Introduction: Effective transition from child and adolescent mental health services (CAMHS) to adult services is one of the main challenges currently facing child psychiatry today The Young Adult 1Programme (YAP) based at St. Patrick's University Hospital Dublin, is a group based day programme especially designed to meet the needs of younger people aged 18–25 and support them through this difficult period. Aims: To examine the effectiveness of participation in YAP for young adults with mental illness. To determine whether participation in particular aspects of the programme prove more beneficial and what factors might be associated with outcome. Method: All patients enrolled in YAP between 1 September 2011 and 31 August 2012 were included in the study. Each patient was assessed using the Health of the Nation Outcome Scales (HONOS) and Global Assessment of Functioning (GAF) rating scale before beginning the programme and after discharge in order to evaluate improvement. The frequency of attendance at individual group sessions was recorded. Patient and illness variables were also recorded, for example demographics, diagnosis. Results: A total of 101 service users were in enrolled in YAP during this 12-month period. Eight service users could not be used for analysis, as they did not have a complete data set, mostly due to failure to attend for discharge HONOS/GAF ratings Using a paired sample t -test, there is a significant reduction in HONOS: Mean df=1.3, s.d. =1.09 (95% CI=1.08–1.53), p <0.001 Using a paired sample t -test, there is a significant increase in GAF: Mean df=9.25, s.d. =7.69 (95% CI=7.66–10.83), p <0.001 Improvements in HONOS and GAF scores are significantly correlated with better attendance at the programme ( p <0.04, <0.00 respectively). Conclusion: More attendance at YAP sessions correlates with better improvement in both HONOS and GAF rating scores.